2009
DOI: 10.2746/095777309x419315
|View full text |Cite
|
Sign up to set email alerts
|

Removal by laparoscopic partial ovariohysterectomy of a uterine leiomyoma assumed to have caused fetal death in a mare

Abstract: Summary A 13‐year‐old pluriparous Dutch Warmblood mare presented to Utrecht University's Department of Equine Sciences 4 weeks after suspected abortion at 3.5 months gestation, to investigate the nature of a uterine mass and persistent vulval discharge. Transrectal ultrasonographic examination revealed copious flocculent fluid and fetal remnants within the uterus and a 5–6 cm heterogenous mass in the uterine wall at the tip of the right horn. Expulsion of fetal parts and resolution of the coexisting endometrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…In some cases, even abdominal pain, secondary endometritis and protrusion of the tumour into the vulva may accompany the persistent haemorrhagic vaginal discharge (Hamir et al. 1989; Heijltjes et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, even abdominal pain, secondary endometritis and protrusion of the tumour into the vulva may accompany the persistent haemorrhagic vaginal discharge (Hamir et al. 1989; Heijltjes et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…; Heijltjes et al . ), it is still an uncommon problem, and there are even fewer reports of leiomyomas in the reproductive tract of the stallion. The authors are aware of only 4 reports of a leiomyoma of the tunica albuginea of the testis in a stallion (Klug and von Lepel ; Johnson and Steinberg ; Wilborn et al .…”
Section: Leiomyoma In the Reproductive Tract Of The Stallionmentioning
confidence: 99%
“…Of the 13 mares discussed in this paper who had an entire uterine horn either removed (Rötting et al 2004) or ligated (McDowell et al 1988, only 4 (30.7%) were able to conceive and carry a foal. Based on the information available to date, the assumptions made by Heijltjes et al (2009) were likely quite correct and the mare in question may have successfully conceived and carried a foal to term.…”
mentioning
confidence: 99%
“…In this issue, Heijltjes et al (2009) describe a laparoscopic partial ovariohysterectomy to remove a uterine leiomyoma in a 13-year-old Dutch Warmblood. Heijltjes et al (2009) reported removing approximately 30% of the right uterine horn in addition to the right ovary and mass. Although the owners elected not to breed the mare again, the authors believed that she could have successfully carried a foal to term.…”
mentioning
confidence: 99%